2022
DOI: 10.1039/d2dt02177c
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium pyridonates: dimerization, redox behaviour, and metal–ligand cooperativity

Abstract: The synthesis, structure, and reactivity of vanadium pyridonate complexes are described. Vanadium(III) pyridonate complexes were accessed through protonolysis and reduction of a tetrakis(amido)vanadium(IV) starting material. Bis(pyridonate) vanadium(IV) precursors could be...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Very recently, Schafer et al also reported the synthesis and reactivity of vanadium(III) pyridonates. 60,61…”
Section: Vanadiummentioning
confidence: 99%
See 3 more Smart Citations
“…Very recently, Schafer et al also reported the synthesis and reactivity of vanadium(III) pyridonates. 60,61…”
Section: Vanadiummentioning
confidence: 99%
“…Very recently, Schafer et al also reported the synthesis and reactivity of vanadium( iii ) pyridonates. 60,61 Complex 17 could be accessed from (THF)V III (Mes) 3 (ref. 61) and V IV (NMe 2 ) 4 (ref.…”
Section: D Transition Metal Complexesmentioning
confidence: 99%
See 2 more Smart Citations